2015
DOI: 10.1186/s13068-015-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

A new generation of versatile chromogenic substrates for high-throughput analysis of biomass-degrading enzymes

Abstract: BackgroundEnzymes that degrade or modify polysaccharides are widespread in pro- and eukaryotes and have multiple biological roles and biotechnological applications. Recent advances in genome and secretome sequencing, together with associated bioinformatic tools, have enabled large numbers of carbohydrate-acting enzymes to be putatively identified. However, there is a paucity of methods for rapidly screening the biochemical activities of these enzymes, and this is a serious bottleneck in the development of enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 39 publications
0
59
0
Order By: Relevance
“…The reproducibility of the assay is shown by the error bars (standard error of mean, SEM, of three replicas). More detailed experiments on the reproducibility of this assay are published elsewhere 8 .…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reproducibility of the assay is shown by the error bars (standard error of mean, SEM, of three replicas). More detailed experiments on the reproducibility of this assay are published elsewhere 8 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…The limitation of this assay kit lies in the detection of endo-enzyme activity, as CPH as well as the ICB substrates are not degradable by exo-enzymes most likely due to steric hindrance arising from the dye and crosslinker molecules 8 .…”
Section: Figure 2 Eight Different Cph Substrates Were Incubated Undementioning
confidence: 99%
See 1 more Smart Citation
“…These observations suggested that cell wall functional fine-tuning associated with border cell release is achieved by coordinated cell wall remodeling rather than by extensive polysaccharide degradation. To test this assumption, we used a recently described set of chromogenic hydrogel substrates developed for screening hydrolytic cell walldegrading enzyme activities (Kra cun et al, 2015). We used a panel of seven chromogenic substrates (chromogenic polymer hydrogel [CPH]) representing major cell wall components and one insoluble chromogenic biomass substrate (pectin-rich orange [Citrus spp.…”
Section: Extensive Cell Wall Degradation Activities Have Not Been Detmentioning
confidence: 99%
“…] peel as a tested substrate for HG-degrading enzymes). As with the CoMPP work, we separately analyzed homogenates of border cells, root tips, as well as washout material, and using this approach, no appreciable enzyme activity was observed, at least not at detection levels reported for CPH substrates (Kra cun et al, 2015) even after 24 h (Supplemental Fig. S5).…”
Section: Extensive Cell Wall Degradation Activities Have Not Been Detmentioning
confidence: 99%